EXPLORING THE SECURITY CHALLENGES IN HOSPITALITY AND TOURISM IN NIGERIA - G.T, KOLAWOLE; Jude, CHIKEZIE; E.O, ADEDEJI; O.L, OMOTAYO; H., ATTAHIRU; AKINTADE, ELIZABETH ABIDEMI (Revista de turism - studii și cercetări în turism, 2020)
Tourism is said to be a business of providing travel, accommodation, food, entertainment for the people who are on travel (Mohamed 2007). Among the consumer variables that affect ones buying behaviour are his mental constructs like: attitude perception, motives and learning.(Kolawole 2011). However, once a consumer is not motivated to buy a product because of some factors that are related to insecurity, much will not be expected in the industry. More so, on the international scene, Nigeria is viewed as a country that is richly blessed culturally. According to the United Nations World Tourism Organization, international tourists arrivals slumped by 1.3 percent in 2001. The changing attitudes of travelers in the wake of various attacks were reflected in the manner in which a number of independent travelers dealt with the fear of insecurity. Likewise in Nigeria, the aspirations and hopes towards a greater Nigeria in tourism receipts has been an illusion.